2001
DOI: 10.1515/rest.2001.107
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Treatment of Paper in Different Environmental Conditions: Chemical, Physical and Microbiological Analysis

Abstract: Brought to you by | University of Queensland -UQ Library Authenticated Download Date | 6/16/15 11:58 PM Gamma Radiation Treatment of Paper 108 included in the trials the Whatman Paper, in order to check, once again, the effects of irradiation on those chemical and physical properties that can be measured only on pure cellulose, for example the degree of polymerisation.The main negative effects of radiation on the paper (observed through viscometric and infrared spectroscopic measurements) are: the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…cellulose and paper) [6][7][8][9] and very few studies have investigated the effect of radiation on parchment [10][11][12][13]. Therefore in this study a number of complementary scientific techniques are used to compare parchment samples before and after exposure to X-rays using XMT to ensure no detectable change is observed.…”
Section: Introductionmentioning
confidence: 99%
“…cellulose and paper) [6][7][8][9] and very few studies have investigated the effect of radiation on parchment [10][11][12][13]. Therefore in this study a number of complementary scientific techniques are used to compare parchment samples before and after exposure to X-rays using XMT to ensure no detectable change is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ionizing radiation on CH materials were studied mainly for cellulosic materials, especially for paper [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and pigments [23][24][25]. Most authors agree that reducing the degree of cellulose polymerization is the main side effect of paper irradiation.…”
Section: Radiation Processing For Cultural Heritage Preservation -Rommentioning
confidence: 99%
“…The handling of books after γ-irradiation may be done safely because γ-rays pass through materials without leaving any residue (Adamo et al, 1998(Adamo et al, , 2001. It also causes no change in the physic-chemical characters of papers (Gonzales, 2002) or in printing compounds (Rocchetti et al, 2002).…”
Section: ‫جدول‬mentioning
confidence: 99%
“…Gamma rays, electromagnetic waves with high penetrating power, pass through materials without leaving any residue, an advantage comparing to other disinfection treatments, since the handling of books and documents may be done safely just after irradiation (Adamo et al, 1998 and2001). Studies demonstrated that the damage in mechanical-physical properties caused by gamma rays on paper was not significant (Adamo et al, 1998 and2001;Gonzalez et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation